Carcinoembryonic antigen-specific, fluorescent image-guided cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for metastatic colorectal cancer. Issue 4 (21st January 2020) - Schaap, D P; Valk, K S; Deken, M M; Meijer, R P J; Burggraaf, J; Vahrmeijer, A L; Kusters, M; Kusters, M; Boogerd, L S F; Schaap, D P; Voogt, E L K; Nieuwenhuijzen, G A P; et al.
Graphical Abstract: This multicentre pilot study investigated the role of peroperative carcinoembryonic antigen (CEA)-specific fluorescence imaging during cytoreductive surgery–hyperthermic intraperitoneal chemotherapy surgery in peritoneal metastasized colorectal cancer. A correct change in peritoneal carcinomatosis index (PCI) owing to fluorescence imaging was seen in four of the 14 included patients. The use of SGM-101 in patients with peritoneally metastasized colorectal carcinoma is feasible, and allows intraoperative detection of tumour deposits and alteration of the PCI. Augmented reality guidance